Effect of plant growth promoting bio-agents (Bacillus sp) on the production of potato (Solanum tuberosum) mini-tubers in north-western Himalaya - SHARMA, ASHWANI KUMAR; VENKATASALAM, E P; KUMAR, VINOD (The Indian Journal of Agricultural Sciences, 2014)
Two plant growth promoting bio-agents, viz. Bacillus cereus (B4) and Bacillus subtilis (B5) were evaluated for production of potato (Solanum tuberosum L.), mini-tubers from micro-plants two potato cultivars, viz. Kufri Giriraj and Kufri Kanchan (red skin tubers) under polyhouse conditions during the autumn (off) seasons of 2008 and 2009. Treatment of micro-plants with both the bio-agents (B4 and B5) proved significantly effective in improving the per cent ground cover, height of plants as well as haulms weight/plant in both the potato cultivars over control. However, no significant effect of these bio-agents was observed on establishment of micro-plants as well as on the number of shoots and compound leaves per plant. B4 bio-agent was found significantly superior in improving the ground cover and haulms weight/plant over B5. Number and yield of mini-tubers/m2 varied significantly between the cultivars and were significantly better with both the bio-agents over control.